The Threshold of Disruption: Assessing the Social Impact of Technologies such as Sora - Quiroga Rodríguez, Elio; Hernández-Pérez, Juan Francisco; Martínez Díaz, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In the digital era, social media and disruptive technologies have transformed the ways in which we interact, consume information, and learn. These innovations have opened new possibilities but have also posed significant challenges, particularly for younger generations. The recent introduction of Sora, OpenAI’s video-generating artificial intelligence, followed by other Generative Artificial Intelligences (GAIs), adds an even more unsettling dimension due to its potential to generate radical and disruptive societal changes. Against this backdrop, understanding the impact and consequences of technological disruptions and assessing their societal repercussions is crucial. To this end, the authors introduce the concept of the Disruptive Factor (Fd), a tool designed to measure and analyse the impact of these disruptive technologies. This approach seeks to raise awareness of the risk/benefit ratio associated with AI and disruptive technologies in general, and to promote informed debate about their regulation and responsible use.